Use of SEM/EDX methods for the analysis of ambient particulate matter adhering to the skin surface. (28th April 2022) - Mirakovski, D.; Damevska, K.; Simeonovski, V.; Nikolovska, S.; Boev, B.; Petrov, A.; Sijakova Ivanova, T.; Zendelska, A.; Hadzi‐Nikolova, M.; Boev, I.; Dimov, G.; Darlenski, R.; et al.
Abstract: Background: The skin is exposed to numerous particulate and gaseous air pollutants. The ones that need particular attention are the particles that adhere to the skin surface, which can later cause direct skin damage. This study aimed to characterize air pollution (AP) particles adhered to the human skin by using scanning electron microscopy (SEM) combined with X‐ray dispersive energy spectrometry (EDX). Methods: Tape stripping was performed from six healthy volunteers exposed to urban AP to collect stratum corneum samples from the cheeks and forehead. The samples were analysed using SEM equipped with EDX system with a silicon drift detector at an accelerating voltage of 20 keV. After the preliminary examination, the particles were located and counted using 1000× magnification. Each particle was analysed, increasing magnification up to 5000× for precise dimension measurement and elemental composition analysis. At least 100 fields or a surface of approximately 1 mm 2 were examined. Results: Particles adhered to the skin were identified in all samples, with a particle load ranging from 729 to 4525. The average area and perimeter of all particles identified were 302 ± 260 μm 2 and 51 ± 23 μm subsequently, while the equivalent circular diameter was, on average, 14 ± 6 μm. The particles were classified into ten groups based on morphology and elemental composition. Chlorides were the most numerous particle group (21.9%), followed by carbonaceous organic particles (20.3%), silicates (18%), carbonates (16.4%), metal‐rich particles (14%), and a minor number of bioaerosols, quartz‐like, and fly ash particles. Conclusion: The SEM–EDX analysis provides evidence of the contamination of exposed skin to various airborne PM of natural or anthropogenic origin. This method may provide new insights into the link between exposure to AP and AP‐induced skin damage.